Correlation between Bethatrophin and 25(OH)D Concentrations in a Group of Subjects With Normal and Impaired Glucose Metabolism - Turkon, H.; Yalcın, H.; Toprak, B.; Demirpençe, M.; Yaşar, H.Y.; Colak, A. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Aim: Inducing beta cell replication is a potential therapeutic approach for the treatment of diabetes mellitus. Recently betatrophin was suggested as a novel stimulator of beta cell proliferation in mice but its role in humans remains to be established. We aimed to investigate betatrophin concentration and its association with metabolic parameters in a group of individuals with normal glucose tolerance, pre-diabetes and diabetes mellitus who had not been previously treated.Methods: A total of 72 subjects were recruited for this cross sectional study: 23 subjects with normal glucose tolerance (NGT), 22 subjects with prediabetes, and 27 subjects with diabetes mellitus (DM). Circulating betatrophin concentration, 75 g oral glucose tolerance test, fasting insulin, glycosylated hemoglobin, 25hydroxy vitamin D and HOMA IR were measured.Results: The difference in betatrophin values did not reach statistical significance between the 3 groups [NGT:206 (176–297)pg/mL, Prediabetes:232 (181–254)pg/mL, DM:245 (205–526)pg/mL, p=0.078]. Betatrophin was negatively significantly correlated with BMI and positively significantly correlated with 25(OH)vitD (p=0.043 and p=0.001 respectively). Multivariate linear regression showed that 25(OH) vitD (β=0.440 p=0.001) and fasting glucose (β=0.003 p=0.038) were variables associated with betatrophin concentration (R2=0.251).Conclusions: In a group of subjects ranging from those with normal glucose tolerance to newly diagnosed diabetes, we found that 25(OH)D and fasting glucose were factors associated with serum betatrophin concentration.
Keywords: betatrophin; OGTT; vitamin D